SLCA Literature Review Data - Atescan Yuksek, Yagmur (Cranfield University, 2025)
Social Life Cycle Assessment (SLCA) has emerged as a crucial element in sustainability discussions, gaining traction in academic research and industry practices. In response to increasing consumer awareness, governmental regulations, and corporate responsibility, sustainable production models have been widely adopted, influencing engineering projects to address not only environmental but also social impacts. This systematic review aims to explore the application of SLCA within the engineering field, focusing on key trends, methodologies, and challenges engineers face when implementing SLCA. To achieve this purpose, 196 peer-reviewed studies published between 2010 and 2024 were analysed through bibliometric and content analysis. The results reveal an increasing trend in SLCA research, with key contributions from energy, mechanical engineering, and chemical engineering fields. Despite its growing relevance, several methodological challenges persist, including a lack of standardisation, data availability issues, and difficulties in integrating SLCA with environmental and economic assessments. The findings of this research can facilitate academic researchers, industrial managers, and policymakers in implementing SLCA practices in engineering applications for a comprehensive sustainability assessment.
Keywords: Social LCA; Engineering; Sustainable Engineering